Biomass gasification: A step toward cleaner fuel and chemicals - Ram M.; Mondal M.K. (My University, 2025)
Fossils fuels are the main energy source, which has led to serious energy crisis, greenhouse gases emission, and other pollutants emission such as SOx, NOx, and so on. As per the international energy agency reports, the CO2 emission by fossil fuels in the year 2019 was 32.1 Gt, which is expected to reach to approximately 42 Gt by the year 2030. This CO2 emission is enormously responsible for global warming and climate change. Therefore, continuous efforts are made for renewable and carbon neutral fuel by several researchers. Biomass is the most suitable candidate for the production of carbon neutral and environmentally friendly renewable biofuels among all available renewable fuels in terms of place of availability and continuity throughout the day. Furthermore, biomass is being used for energy from the invention of fire. It is still being used for energy production in rural areas. However, only 10%-14% of the total world's energy supply has been fulfilled by biomass. Scientific efficient utilization of biomass for chemicals and fuels needs a suitable conversion technology. There are many biomass conversion technologies available for these purposes. Conversion technology depends on the types of biomass. Furthermore, gasification is the prominent technology for the biomass with moisture content less than 30% since its main product is in the gaseous form known as synthesis gas, which can be converted in different chemicals. In early days, gasification was limited to coal; then researchers move toward biomass gasification. After continuous approach toward the rectification of bottlenecks, researchers increased the energy density of biomass to some extent. However, the main bottleneck still persisting for the utilization of biomass is low concentration of H2 in synthesis gas. Therefore, it requires process upgradation and enrichment of end product. This chapter starts with biomass availability and characterization. Furthermore, it gives an overview of all types of gasification process. Then, effects of all possible parameters on main products have been discussed. Finally, an outline of the enrichment of end products has been illustrated. © 2022 Elsevier Inc. All rights reserved.